2000
DOI: 10.1177/088307380001500902
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Treatment Protocols and the Central Nervous System: Significant Cure With Significant Neurotoxicity

Abstract: Methotrexate can influence the central nervous system through several metabolic toxic pathways. These effects can be categorized as immediate, acute to subacute, or chronic neurologic syndromes. The acute to subacute syndrome occurs frequently in acute lymphoblastic leukemia treatment protocols, generally manifesting with focal neurologic signs and changes seen on magnetic resonance imaging and single photon emission computed tomography. While in some patients the neurotoxicity is transient and benign and allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 35 publications
0
66
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30] Moreover, under description owing to insufficient means for monitoring is possible. When limited to grade 3-4 episodes, the neurological complications incidence in our series is 3.7%.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30] Moreover, under description owing to insufficient means for monitoring is possible. When limited to grade 3-4 episodes, the neurological complications incidence in our series is 3.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Lesnik et al (1998) demonstrated cerebellar-frontal subsystem changes on structural MRI in children with ALL treated before the age of 5 with chemotherapy only. Methotrexate is the cytostatic drug mostly implicated in central neurotoxicity in children with ALL (Shuper et al, 2000). Cerebral white matter changes (Chu et al, 2003;Dambska & Laure-Kamionowska, 1999;Surtees et al, 1998), neuronal damage (Chu et al, 2003;Quinn et al, 1998;Van Gool et al, 2000) and neurotransmitter abnormalities (Madhyastha et al, 2002) have been described in children treated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxicity can present in acute, subacute, or chronic forms. 6 Chronic MTX neurotoxicity develops slowly and may progress to permanent neurologic impairment, dementia, and gradual functional decline. 6 Acute toxicity may include headache, nausea, lethargy, altered mental status, blurred vision, seizure, or increased intracranial pressure developing within 1 day of administration.…”
Section: Sectionmentioning
confidence: 99%
“…6 Chronic MTX neurotoxicity develops slowly and may progress to permanent neurologic impairment, dementia, and gradual functional decline. 6 Acute toxicity may include headache, nausea, lethargy, altered mental status, blurred vision, seizure, or increased intracranial pressure developing within 1 day of administration. Stroke-like symptoms have a subacute presentation 5-15 days after IV or intrathecal administration, and have been estimated to occur in approximately 2% of patients receiving MTX.…”
Section: Sectionmentioning
confidence: 99%